Molecular mechanisms of Phytophthora sojae avirulence effectors escaping host recognition - Hou, Xiaoyuan; He, Zheng; Che, Zhengzheng; Li, Hengjing; Tan, Xinwei; Wang, Qunqing (Frontiers in Microbiology, 2023)
Phytophthora sojae is a well-known destructive oomycete pathogen, which causes soybean stem and root rot and poses a serious threat to global food security. Growing soybean cultivars with the appropriate resistance to P. sojae (Rps) genes are the primary management strategy to reduce losses. In most Phytophthora pathosystems, host resistance protein encoded by a specific R gene in the plant recognizes corresponding RxLR effector protein, encoded by an avirulence gene. This gene-for-gene relationship has been exploited to help breeders and agronomists deploy soybean cultivars. To date, 6 Rps genes have been incorporated into commercial soybean germplasm and trigger plant immunity in response to 8 P. sojae avirulence effectors. The incorporation of Rps genes in the soybean population creates selection pressure in favor of novel pathotypes of P. sojae. The 8 avirulence genes evolved to evade the host immune system, driven by genetic selection pressures. Understanding the evading strategies has important reference value for the prevention and control of Phytophthora stem and root rot. This investigation primarily highlights the research on the strategies of P. sojae avirulence effector evasion of host recognition, looking forward to creating durable resistance genes and thereby enabling successful disease management.